The Art of the True Self: Using Art Therapy as a Means of Self-Discovery - Kilpo, Alison M. (My University, 2013)
Participation in the act of creating art opens one up to a realm of possibilities for the betterment of the individual. The field of art therapy was established on this idea, the idea that the creative process has the potential to help people. The ways in which art therapy helps people is numerous - self-expression, help overcoming difficult situations, exploration and discovery of potential are only a few examples. Of the many ways art therapy may help people, one all-encompassing idea is art therapy helps a person understand who they are, by exploring their life's journey and seeking truths. Art therapy helps a person establish and understand who they are as an individual in a world full of individuals. Through the use of art therapy, a person uses art as a tool to process their past, present, and future and embrace the journey life has taken them on to become who they are today. Art therapy allows for exploration of the self and for the discovery of the individual - of being true to oneself. I have embarked on this journey of self-discovery over the course of the last two years. I have came to a deep understanding of who I am as an individual through art therapy and now I am using art therapy to aid others in their own process of self-discovery and self-truth.
Keywords: Art Therapy; Visual Arts